Peering through a Looking Glass: Deconstructing Teacher Candidate Assumptions Using Dispositions. Issue 2 (8th April 2022) - Schussler, Deborah L.; Bercaw, Lynne
Abstract: The purpose of this qualitative study was to examine how teacher candidates' responses to a case provided an opportunity to make inferences about their dispositions and thus, build awareness of their assumptions. Fourteen teacher candidates responded to a dilemma-embedded case at the beginning and end of their student teaching semester. Candidate responses were coded using a framework of three disposition domains–intellectual, cultural, and moral. Results suggest that over time, candidates demonstrated greater integration of concepts and refined perspectives, encompassing increased awareness of the sociocultural and moral aspects of teaching while moving beyond technical pedagogical practice. However, candidates did not explicitly identify their assumptions. Implications for teacher education include providing scaffolded opportunities to build self-awareness, like archiving candidates' thinking when they respond to a case multiple times and combining field experience with cases and opportunities to reflect about cultural worldviews and underlying values.